THE DEVELOPMENT OF ISLAMIC INTEGRATED BIOCHEMICAL TEACHING MATERIALS USING FOUR STEPS TEACHING METHOD - Siti Suryaningsih; Buchori Muslim; Via Fitriani (Jurnal Tadris Kimiya, 2020)
Islamic-integrated learning is one of the implementations in realizing UIN Syarif Hidayatullah Jakarta’s vision. So, the teaching materials which are integrated with Islamic features are needed. This research aims to develop a biochemistry teaching material in the form of an Islamic-integrated enrichment book specifically on the theory of amino acid and protein that is feasible to be used. The method used in this study is the research and development method through the Four Steps Teaching Material Development (4S-TMD), which consists of selection, structurization, characterization, and reduction. The research data are obtained from the validation of Islamic-integrated chemical study by expert lecturers. The validation result was analyzed using the Guttman Scale, a comprehensive test of concept in the form of the main idea writing test on 60 students of 2016 generation of chemistry education were analyzed by giving a score of 1 for each correct answer, and a score of 0 for wrong answers, and the book's feasibility test in terms of language, presentation, performance, and graphic validated by media expert lecturers, and were analyzed using the Rating Scale. The validation of the Islamic-integrated chemistry shows that all concepts are powerful and worthy of being presented, with the percentage of 91.4%. The comprehensive test of concept shows that all of the concepts have a high level of comprehension. The percentage of students’ comprehensions of all concepts amounted to 92.7%, and all of the concepts are included in the easy category. Therefore there is no need for a reduction phase. Based on the results of the feasibility test of the book, it is obtained the average percentage of 85.5%, which indicates that the Islamic-integrated enrichment book of amino acid and protein material is suitable to be used in the learning of Islamic-integrated biochemistry course to increase student knowledge on biochemical concepts through Islamic aspects which can increase the faith to Allah SWT.